The traceability of animal meals in layer diets as detected by stable carbon and nitrogen isotope analyses of eggs - Denadai,JC (2008)
The aim of this study was to trace the inclusion of animal meals in layer diets by analyzing eggs and their fractions (yolk and albumen) using the technique of carbon and nitrogen isotopes. Two-hundred and eighty-eight (288) 73-week-old Shaver White layers, never fed animal ingredients, were randomly distributed in six treatments with six replicates each. The treatments were: control - corn and soybean meal based diet and five other experimental diets including bovine meat and bone meal (MBM); poultry offal meal (POM); feather meal (FM); feather meal and poultry offal meal (OFM), and poultry offal meal, feather meal, and meat and bone meal (MBOFM). The isotopic results were submitted to multivariate analysis of variance. Ellipses were determined through an error matrix (95% confidence) to identify differences between treatments and the control group. In the albumen and yolk of all experimental treatments were significantly different from the control diet (p < 0.05). In summary, the stable isotope technique is able to trace the animal meals included in layer feeds in the final product under these experimental conditions.